Use of the Z-DNA binding domain of ADAR1 as a probe for nucleic acids in left-handed conformation - Li, Heng (2009)
Both DNA and RNA can be in Z-conformation. Compared to classical B-DNA conformation, Z-DNA is in a higher energy state and studied extensively, so far mainly in vitro. It has been recognized that Z-DNA plays roles in many biological activities, including regulation of transcription, chromatin remodeling, genetic instability, etc. Bioinformatics analyses and experimental studies on particular genomic loci suggest that the Z-DNA forming sequences are enriched in gene regulatory regions, where the formation of Z-DNA is drived by transcription-induced negative supercoiling. However, the global distribution of Z-DNA in the human genome in vivo is still experimentally elusive, due to instable nature of Z-DNA and lack of Z-DNA specific probe. Here, we show for the first time the distribution of Z-DNA hotspots in the genome of cultured human cancer cells A549 by exploiting the Zα domain from human ADAR1 (ZαADAR1, simplified as Zα for convenience in the thesis) as a Z-DNA specific probe with a novel experimental strategy. A protocol for in vitro chromatin affinity precipitation (ChAP) was developed and a Z-DNA library was constructed and sequenced. In total, 186 Z-DNA hotspots were identified. Enrichment of hotspots in gene regulation regions was not found. Unexpectedly, 46 hotspots localize to the centromeric regions. Further examination on hotspots therein suggests that Z-DNA hotspots are strongly correlated with high occurrences of SNPs (single nucleotide polymorphism). Bioinformatics analysis using a Z-DNA prediction program shows that most of these Z-DNA forming hotspots (143 out of 186) could be transited to Z-conformation only at σ < - 0.08, suggesting particular regions in the centromeres contain high negative superhelical torsional strain. Genetic instability and gene conversion promoted by Z-DNA provide a new clue for the rapid evolution of the centromere.